Zagospodarowanie pozostałości z termicznego przetwarzania odpadów komunalnych w Polsce = The utilization of residues from the thermal treatment of the municipal waste in Poland - Poniatowska, Agnieszka; Andrzejewska-Górecka, Dorota Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Considering the existing and planned inceneration plants we will soon have in Poland nearly 0.5 million Mg of waste from this plant need to safe treatment. Most of the generated waste are ashes and slags, which are partly used for the production of construction aggregates. In Poland, nobody has passed the procedure of end-of-waste for this waste yet. We should like in Czech Rpublic get the REACH procedure for slags and ashes from the incineration of municipal waste. Then we will have products, which we can use in construction.
Keywords: popioły; żużle; spalarnia odpadów; przetwarzanie odpadów pospalarnianych; ashes; slags; inceneration plant; methods of treatment the waste from incineration plant